NILAI PERUSAHAAN : EFEK DARI DEBT TO ASSET, LIQUIDITY DAN INTELLECTUAL CAPITAL DI MEDIASI OLEH RETURN ON ASSET: (Studi Empiris Pada Perusahaan Wholesaler and retailer Yang Terdaftar Di BEI Periode Tahun 2014-2017) - Sumarni Sumarni; Abdul Halim; Djuni Farhan (STIE Mahardhika, 2020)
This research aims to test and explain the influence of Debt To Asset, Liquidity and Intellectual Capital against Return On Asset. Both the influence of langsungDebt To Asset, Liquidity and Intellectual CAPITATERHADAP corporate values as well as the indirect influence of Debt To Asset, Liquidity and Intellectual Capital towards the company's value through Return On Asset. Sampling techniques of this study using the purposive sampling method. The data used is quantitative data in the form of annual financial statements listed on the Indonsia Stock Exchange. The independent variables in this study are DEBT To Asset, Liquidity also Intellectual Capital and corporate values as dependent variables as well as Return On Asset as mediation variables with total samples that meet the research criteria as many as 18 companies of Wholesaler and retailer period 2014 S/d 2017 and analysis of data using path analysis. The results of this study show that Debt To Asset, Liquidity and Intellectual Capital have an effect on Return On Asset. As well as directly Debt To Asset, Liquidity and Intellectual Capital are influential in the company's value. Also indirectly Debt To Asset, Liquidity and Intellectual Capital affect the value of the company through Return On Asset.